2018
DOI: 10.1002/vnl.21687
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, morphological, and thermal properties of poly(vinyl chloride)/low‐density polyethylene composites filled with date palm leaf fiber

Abstract: This article investigates the mechanical, morphological, and thermal properties of poly(vinyl chloride) (PVC) and low‐density polyethylene (LDPE) blends, at three different concentrations: 20, 50, and 80 wt% of LDPE. Besides, composite samples that were prepared from PVC/LDPE blend reinforced with different date palm leaf fiber (DPLF) content, 10, 20, and 30 wt%, were also studied. The sample in which PVC/LDPE (20 wt%/80 wt%) had the greatest tensile strength, elongation at break, and modulus. The good thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…The valorization of date palm fiber (DPF) [4,5] and dune sand (DS) [6,7] in material engineering is an important economic activity in northern Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The valorization of date palm fiber (DPF) [4,5] and dune sand (DS) [6,7] in material engineering is an important economic activity in northern Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers reported the incorporation of different polymers in PVC induced high thermal and mechanical performance [26-28]. Our previous experimental results revealed that thermal stability of the PVC/LDPE blend was improved signi cantly by increasing the LDPE loading to values above 50 wt% [29]. To the best of our knowledge there are no reports of degradation behavior of PVC, considering the synergistic effects of mixed metal stabilizers (CaSt 2 /ZnSt 2 ) with different concentrations and different ratios of calcium/zinc stearates, Calcium carbonate (CaCO 3 ) as micro-ller and recycled low-density polyethylene (r-LDPE).…”
Section: Introductionmentioning
confidence: 98%
“…These properties limit their application. The mixing of these polymers [6][7][8][9][10] makes it possible to strengthen a number of operational characteristics (e.g., the elastic modulus, glass transition temperature, impact resistance, and thermal stability) depending on the ratio of the components in the mixture and their initial characteristics. Of significant interest is the effect of the thermal stabilization of polyvinyl chloride (PVC) at low PE contents [10][11][12][13] due to interchain crosslinking of macroradicals formed during the mixing of the components in the melt in the temperature range from 150 to 180 С.…”
Section: Introductionmentioning
confidence: 99%